City of bones - Clare, Cassandra (New York Margaret K. McElderry Books, 2008)
Suddenly able to see demons and the Shadowhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizarre world when her mother disappears and Clary herself is almost killed by a monster
Includes excerpt from book two in The mortal instruments: City of ashes and a sneak peek of the first book in Cassandra Clare's Infernal devices trilogy
Ages 14 up
1
NEW, LITERATURE
Keywords: Demonology -- Juvenile fiction; Demonology; Magic -- Juvenile fiction; Magic; Paranormal fiction; Paranormal fiction; Demonology -- Fiction; Horror stories; Supernatural -- Fiction; New York (N.Y.) -- Fiction; New York (State) -- New York; Fiction; Juvenile works